Sustainable Concrete with Coir and Crushed Coconut Shells: Workability and Strength Performance - Joseph , Kuta; Samuel , Waweru; B. , Sabuni; Edwin , Kanda; Jared , Okungu (Multidisciplinary Journal of Technical University of Mombasa, 2025)
The increasing demand for sustainable materials within the construction industry has heightened interest in alternative aggregates for concrete, motivated by escalating costs and environmental concerns associated with conventional natural aggregates. The overexploitation of these resources has led to scarcity and increased expenses, underscoring the necessity for cost-effective solutions that maintain concrete's performance and structural integrity. Furthermore, the improper disposal of agricultural by-products, such as coir and crushed coconut shells, exacerbates waste management challenges and poses environmental risks. This paper aimed to evaluate the workability and compressive strength of concrete incorporating coir fibers and crushed coconut shells as aggregate replacements. The study was conducted in the counties of Kilifi, Mombasa, and Kwale in Kenya, with a focus on the utilization of coir and crushed coconut shells in concrete mixtures. The experimental design involved the preparation of concrete mixtures with coir percentages of 0.1%, 0.2%, and 0.3%, along with crushed coconut shell aggregates at 10%, 20%, and 30% by volume. Key variables assessed included workability—measured through the Slump Test, Flow Table Test, and Vebe Consistometer. The mechanical properties, were evaluated via compressive strength and durability tests. A total of 72 concrete cubes and 72 short beams were prepared using locally sourced materials to ensure relevance to regional practices. Data collection adhered to standardized protocols, and the validity and reliability of measurement instruments were established through expert reviews and consistency checks. The study demonstrates that incorporating crushed coconut shell aggregates (CCSA) into concrete significantly reduces workability due to increased water demand and lower density. Conversely, adding coir fibers enhances workability, although excessive coir can negatively affect it. Compressive strength reduces making CCSA up to 20%, the minimum structurally usable mix, with, but further additions produces compression strength only suitable for non-structural use. The inclusion of 0.3% coir fibers further boosts compressive strength, especially with CCSA. This study recommends limiting coir to 0.3% for optimal workability and promoting CCSA use up to 20%, along with further research on their microstructural impacts.
Keywords: Workability, Compressive Strength, Sustainable Concrete, Coir, Crushed Coconut Shells, Partial Aggregate Replacements